PKM Pelatihan Peningkatan Kinerja TIM PKK Pada Desa Payageli - Zahri, Cut; Nasution, Umar Hamdan; Sinaga, Kariaman; Sopang, Fandi Iksandar; Zulkarnaen, Mierna; Junaidi, Listya Devi (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
The importance of the performance of the PKK cadre team can make it easier to achieve organizational goals. If these resources can be mobilized quickly, so that they can be used and the organization can run effectively and efficiently, it can be said that an organization's ability to fulfill its stated goals depends on teamwork in building a climate of collaboration.  This service aims to inspire the PKK women's group in Payageli Village to be able to manage their group more effectively and efficiently. The service was carried out by providing team performance training to the PKK women's group in Payageli Village.  The process includes observation, socialization, training, as well as monitoring and assessment as the final stage. The material offered is information regarding basic human resource management concepts, member recruitment and selection processes, human resource development, motivation and leadership and effective communication within teams. To help the PKK women's group in Payageli Village in managing the organization, creating a management structure, and developing the talents of PKK cadres, it is hoped that this can be carried out through this service activity. Based on the results of this activity, PKM participants gained knowledge and knowledge about how to improve the performance of the PKK team to be even better.